Amyotrophy Induced by a High-Fat Diet Is Closely Related to Inflammation and Protein Degradation Determined by Quantitative Phosphoproteomic Analysis in Skeletal Muscle of C57BL/6 J Mice. Issue 2 (16th October 2019) - Sun, Ya-nan; Huang, Jia-qiang; Chen, Zhong-zhou; Du, Min; Ren, Fa-zheng; Luo, Jie; Fang, Bing
ABSTRACT: Background: Ectopic fat accumulation in skeletal muscle results in dysfunction and atrophy, but the underlying molecular mechanisms remain unclear. Objective: The aim of this study was to investigate the effects of a high-fat diet (HFD) in modulating the structure and energy metabolism of skeletal muscle and the underlying mechanisms in mice. Methods: Four-week-old male C57BL/6 J mice ( n = 30) were allowed 1 wk for acclimatization. After 6 mice with low body weight were removed from the study, the remaining 24 mice were fed with a normal-fat diet (NFD; 10% energy from fat, n = 12) or an HFD (60% energy from fat, n = 12) for 24 wk. At the end of the experiment, serum glucose and lipid concentrations were measured, and skeletal muscle was collected for atrophy analysis, inflammation measurements, and phosphoproteomic analysis. Results: Compared with the NFD, the HFD increased ( P < 0.05) body weight (35.8%), serum glucose (64.5%), and lipid (27.3%) concentrations, along with elevated ( P < 0.05) expressions of the atrophy-related proteins muscle ring finger 1 (MURF1; 27.6%) and muscle atrophy F-box (MAFBX; 44.5%) in skeletal muscle. Phosphoproteomic analysis illustrated 64 proteins with differential degrees of phosphorylation between the HFD and NFD groups. These proteins were mainly involved in modulating cytoskeleton [adenylyl cyclase-associated protein 2 (CAP2) and actin-α skeletal muscle (ACTA1)], inflammation [NF-κB-activating protein (NKAP) and serine/threonine-protein kinase RIO3 (RIOK3)], glucose metabolism [Cdc42-interacting protein 4 (TRIP10); protein kinase C, and casein kinase II substrate protein 3 (PACSIN3)], and protein degradation [heat shock protein 90 kDa (HSP90AA1)]. The HFD-induced inhibitions of the insulin signaling pathway and activations of inflammation in skeletal muscle were verified by Western blot analysis. Conclusions: Quantitative phosphoproteomic analysis in C57BL/6 J mice fed an NFD or HFD for 24 wk revealed that the phosphorylation of inflammatory proteins and proteins associated with glucose metabolism at specific serine residues may play critical roles in the regulation of skeletal muscle atrophy induced by an HFD. This work provides information regarding underlying molecular mechanisms for inflammation-induced dysfunction and atrophy in skeletal muscle.